Accidents and injuries related to paragliding on mount Babadağ, Turkey: A cross-sectional study - Ömer Faruk Karakoyun; Yalcin Golcuk (Turkish Journal of Emergency Medicine)
OBJECTIVES: In light of the growing popularity of paragliding, this cross-sectional study aimed to investigate the epidemiology of paragliding accidents, providing insights into the types and severity of injuries sustained as well as the body regions most commonly affected. METHODS: This cross-sectional retrospective study utilized data on adverse paragliding events on Mount Babadağ in Turkey, collected by the Muğla Sports Tourism Board (STB) between January 2020 and December 2021, with data sources including out-of-hospital STB forms and in-hospital electronic health records. RESULTS: Out of 241,420 paragliding flights, a total of 44 accidents were identified, with only three resulting in fatalities. Most of the accidents occurred during take off and landing, but the deadliest phase was during flight. The majority of accidents were of low severity, with a median National Advisory Committee for Aeronautics score of 1 (interquartile range [IQR] 1–3) and a median injury severity score of 1 (IQR 1–7.75). The lower limb was the most commonly injured body part, accounting for 55.8% of injuries, followed by the upper limb at 30.8%. CONCLUSIONS: Despite being considered an extreme sport, paragliding carries a relatively low risk of accidents and serious injuries, owing to advancements in training, equipment inspection, and protective gear.